Ethnolinguoculturological Studies in Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Research in ethnolinguocuturology covers a wide range of topics, including language acquisition, bilingualism, language policies, language attitudes, intercultural communication, and cultural identity. The article discusses ethnolinguoculturological studies in Linguistics and contribution of linguists to the development of Ethnolinguoculturology.